2016
DOI: 10.1186/s13014-016-0607-9
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated partial breast irradiation using robotic radiotherapy: a dosimetric comparison with tomotherapy and three-dimensional conformal radiotherapy

Abstract: BackgroundAccelerated partial breast irradiation (APBI) is a new breast treatment modality aiming to reduce treatment time using hypo fractionation. Compared to conventional whole breast irradiation that takes 5 to 6 weeks, APBI is reported to induce worse cosmetic outcomes both when using three-dimensional conformal radiotherapy (3D-CRT) and intensity-modulated radiotherapy (IMRT). These late normal tissue effects may be attributed to the dose volume effect because a large portion of the non-target breast tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
1
13
0
4
Order By: Relevance
“…Furthermore, the fiducial-based synchrony tracking method used by CyberKnife allows adding a minimal margin to CTV when creating PTV, allowing for greater spare of skin surface, chest wall, and pectoralis muscles. In general, we used a greater margin between CTV and PTV than that considered by Rault et al [ 29 ]: however our PTV dimensions were consistent with other experiences [ 30 , 38 ], but to reduce the skin dose we often applied a smaller margin near the skin to keep a margin of 5 mm between skin and PTV. Moreover, CyberKnife offers the possibility to fractionate the dose through a large number of beams (in our experience from 56 to 325) allowing distribution of the skin dose on a larger area, making the treatment more acceptable.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, the fiducial-based synchrony tracking method used by CyberKnife allows adding a minimal margin to CTV when creating PTV, allowing for greater spare of skin surface, chest wall, and pectoralis muscles. In general, we used a greater margin between CTV and PTV than that considered by Rault et al [ 29 ]: however our PTV dimensions were consistent with other experiences [ 30 , 38 ], but to reduce the skin dose we often applied a smaller margin near the skin to keep a margin of 5 mm between skin and PTV. Moreover, CyberKnife offers the possibility to fractionate the dose through a large number of beams (in our experience from 56 to 325) allowing distribution of the skin dose on a larger area, making the treatment more acceptable.…”
Section: Discussionsupporting
confidence: 58%
“…All authors comparing CyberKnife versus other techniques, i.e. 3D-CRT, IMRT and tomotherapy, concluded that CyberKnife can achieve a highest level of PTV coverage and, generally, the deepest dose gradient with better dose sparing of organs at risk and, in particular, of the homolateral breast [ 27 29 , 39 ]. Consequently, the involved tissue volume can be reduced by treatment with CyberKnife [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated partial breast irradiation (APBI) is an effective alternative to standard whole breast irradiation (WBI) in selected early-stage breast cancer patients undergoing breast conservation therapy [ 1 6 ]. Recently developed stereotactic partial breast irradiation (S-PBI) allows 1–5 treatment fractions by delivering a high biologically potent dose to the target, while sparing adjacent critical organs and normal tissue [ 1 , 7 9 ]. With S-PBI tumoricidal doses, accurate and precise dose delivery is critical to achieve high treatment quality.…”
Section: Introductionmentioning
confidence: 99%
“…Helical tomotherapy is a modality of IMRT delivered by a continuously moving slip ring gantry in synchrony with the couch motion, and with a fan radiation beam modulated by a binary multi‐leaf collimator. The application of mega‐voltage computed tomography (CT) provides a viable solution to adaptive radiotherapy and dose‐guided radiotherapy …”
Section: Introductionmentioning
confidence: 99%